The Implementation of Mind Mapping on Chemical Bond Learning Assisted by Information Technology towards the Students’ Learning Outcomes in Class X MIA 1 at SMA Negeri 1 Sindue - Awanda Awanda; Tahril Tahril; Minarni R. Jura (Universitas Tadulako, 2020)
This study aimed to determine the influence of the implementation of mind mapping on learning of chemical bonding assisted with information technology toward learning outcomes of students in the Class X1 Science at SMA 1 Sindue. This study was a quasi-experiment with non-randomized pretest-posttest control group design. Sampling was based on special consideration (purposive sampling) with a sample of students of class X1 Science as the experimental class and class X2 Science as the control class. The instrument of this study was a test of learning outcomes. Data of the results was tested using statistical analysis of one-party t-test with prerequisite tests of normality and homogeneity tests. The data analysis obtained an average score of learning outcomes in the experimental class was 77.12 and in the control class was 67.6. Based on the hypothesis test with the t-test statistic of two parties obtained tcount of 10.89 and ttable of 1.95 at α 0.05. In this case, H1 was accepted and H0 was rejected because tcount was in the area of ​​ H0 rejection. This showed that there were differences in students’ learning outcomes through the implementation of mind mapping and conventional in learning of students in 10th grade at SMA 1 Sindue.